Germany and the United States in coronavirus distress: Internal versus external labour market flexibility - Alexander Herzog-Stein; Patrick Nüß; Lennert Peede; Ulrike Stein (Journal for Labour Market Research, 2022)
Germany and the United States pursued different economic strategies to minimise the impact of the Coronavirus Crisis on the labour market. Germany focused on safeguarding existing jobs through the use of internal flexibility measures, especially short-time work (STW). The United States relied on a mix of external flexibility and income protection. On this basis, we use macroeconomic time series to examine the German strategy of securing employment through internal flexibility by contrasting it with the chosen strategy in the United States. In Germany, temporary cyclical reductions in working hours are mainly driven via STW. US unemployment rose at an unprecedented rate, but unlike in previous recessions, it was mostly driven by temporary layoffs. However, a closer look at the blind spots of the chosen strategies in both countries showed that despite the different approaches, people in weaker labour market positions were less well protected by the chosen strategies.
Keywords: E24; E32; J08; J20; 330; Coronavirus recession; Covid-19 pandemic; External flexibility; Great recession; Internal flexibility; Safeguarding employment; Short-time work; Temporary layoffs; Unemployment; Working-time reduction